N-Butyl-2-Cyanoacrylate versus Microspheres on Weight Change and Ghrelin Expressions in Swine Bariatric Embolization Model - Won Seok Choi; Young Suk Park; Kun Yung Kim; Chong-ho Lee; Minuk Kim; Chang Jin Yoon; Jae Hwan Lee (CVIR Endovascular)
Abstract Background Obesity is a global health challenge, leading researchers to explore innovative treatments. Bariatric arterial embolization (BAE), which blocks blood flow to parts of the stomach, shows promise for weight management by affecting hunger hormones like ghrelin. This study aimed to compare the efficacy and safety of n-butyl-2-cyanoacrylate (NBCA) and microspheres in suppressing weight gain and ghrelin expression after BAE in a swine model. Materials and Methods Fifteen healthy juvenile male farm pigs were randomly allocated into three groups: NBCA embolization (n = 5), microsphere embolization (n = 5), and a control group (n = 5). Embolization targeted the right, left, and short gastric arteries. Weight and fasting plasma ghrelin levels were monitored weekly for 16 weeks. Gastric endoscopy was performed 1 and 4 weeks post-BAE, and each animal's ghrelin-expressing cells in the stomach's fundus, body, and antrum were analyzed. Results By week 16, the NBCA group showed lower weight gain (58.4 ± 17.8%) compared to that in the microsphere (114.0 ± 0.0%; P < .001) and control groups (123.9 ± 18.1%; P < .001). The NBCA group had lower mean ghrelin-expressing cell densities in the gastric fundus (P < .001), body (P = .002), and antrum (P = 0.003) compared to those in the control group, and lower ghrelin-expressing cell densities in the fundus compared to those in the microsphere group (P < .001). Endoscopy at 1-week post-BAE revealed gastric ulcers in 2 pigs in the NBCA group (40%) and all pigs (100%) in the microsphere group, which healed by week 4; no ulcers were found in the control group. Conclusions In a swine model of bariatric arterial embolization, NBCA was more effective than microspheres in reducing weight gain and ghrelin expression in the stomach fundus, indicating its potential for managing obesity through BAE.